Implementasi Pembelajaran Kitab Risalat Adab Suluk al-Murid dalam Membentuk Karakter Siswa melalui 7 Kebiasaan Baik: Studi di SMPIQu Al-Bahjah Cianjur - Amaliyah, Dede Siska; Albi Nur Paisal (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Character formation is a fundamental component of Islamic education, particularly in responding to the growing challenges of moral decline and the weakening of students’ manners in contemporary learning environments. This study aims to analyze the implementation of the classical text Risalat Adab Suluk al-Murid in shaping student character through the integration of seven good habits at SMPIQu Al-Bahjah Cianjur. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation to explore how the values of adab are internalized and reflected in students’ daily behavior. The findings indicate that the learning of this classical text strengthens students’ discipline, respect toward teachers, sense of responsibility, and enthusiasm for learning. The internalization process occurs not only during classroom activities but also through daily routines such as morning habits, worship practices, time management, and social interactions within the school environment. The seven good habits function as a practical framework that reinforces the application of sufistic values taught in the text, allowing students to translate moral teachings into consistent actions. Teachers play a crucial role as role models who guide, demonstrate, and cultivate these values through continuous supervision and exemplary conduct. The study concludes that classical Islamic text-based learning offers an effective strategy for enhancing student character within modern Islamic educational settings. The implications highlight the need for schools to strengthen adab-centered curricula, cultivate ethical school culture, and promote collaboration among teachers, institutions, and families to ensure sustainable character development.